Answered

Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

This equation has one solution.

3(x – 2) + 4x = 10(x + 1)
what is the solution?
-5
-2
-16/3
-16/7


Sagot :

Answer: -16/3

Step-by-step explanation:

[tex]3(x - 2) + 4x = 10(x + 1)\\3x - 2(3) + 4x = 10x +1(10)\\3x - 6 + 4x = 10x + 10\\7x - 6 = 10x + 10\\7x - 10x = 10 + 6\\-3x = 16\\x = \frac{16}{-3} =-\frac{16}{3}[/tex]

Answer:

-16/3

Step-by-step explanation:

3(x – 2) + 4x = 10(x + 1)

Step 1 distribute the 3 to the x and -2

Outcome: 3x - 6 + 4x = 10(x + 1)

Step 2 distribute the 10 to the x and 1

Outcome: 3x - 6 + 4x = 10x + 10

Step 3 combine like terms

Outcome: 7x - 6 = 10x + 10

Step 4 add 6 to both sides

Outcome: 7x = 10x + 16

Step 5 subtract 10x from both sides

Outcome: -3x = 16

Step 6 divide both sides by -3

Outcome: x = -16/3